Behavioral Intervention Technologies and Psychotherapy with Youth: A Review of the Literature - Bunge, E.L.; Dickter, B.; Jones, M.K.; Alie, G.; Spear, A.; Perales, R. (Current Psychiatry Reviews, 2016)
The dominant model of delivering psychological interventions is face-to-face (F2F) in oneto- one psychotherapy. Behavioral Intervention Technologies (BITs) may have the capacity to expand delivery models and/or increase the outcomes of therapy. This article is a systematic review of the available literature on BITs for children and adolescents with DSM-5 mental health diagnoses. All articles on EBSCOhost published between 1st January 2000 and 31st December 2014 referencing terms related to youth, BITs, and therapy were collected for analysis (n=7179). After inclusion/exclusion criteria were applied, 53 articles were included in the review, discussing BIT interventions for Anxiety, Depression, Obsessive-Compulsive Disorder, Attention-Deficit/Hyperactivity Disorder, Conduct Disorder, and Oppositional Defiant Disorder. The review found general support for BITs as interventions for child and adolescent disorders. Limitations of the current research and suggestions for future directions are discussed.
Keywords: systematic review